2006
DOI: 10.1007/s10597-006-9057-4
|View full text |Cite
|
Sign up to set email alerts
|

Remission from Pathological Gambling among Hispanics and Native Americans

Abstract: This community survey studied remission from pathological gambling (PG) among American Indian (AI) and Hispanic American (HA) veterans. Remission was defined as having a lifetime diagnosis of PG, but no gambling symptoms in the last year. Sample consisted of 1624 AI and Hispanic veterans. Instruments included demographic data, the computer-based algorithmic Quick Diagnostic Interview Schedule Symptom, and three symptom checklists, one each for substance related problems (MAST/AD), anxiety and depressive sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Population-based studies identified higher cortisol levels in women [51]; cardiovascular disease [52]; nightmares [16]; substance use disorders [41]; and bodily pain [24]. Community-based studies identified depressive symptoms [39]; pathological gambling [34, 53]; lifetime nicotine dependence [34, 44]; and anti-social personality disorders [34]. Clinical studies identified substance abuse [38, 47]; alcohol abuse [47]; and other mental disorders [38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Population-based studies identified higher cortisol levels in women [51]; cardiovascular disease [52]; nightmares [16]; substance use disorders [41]; and bodily pain [24]. Community-based studies identified depressive symptoms [39]; pathological gambling [34, 53]; lifetime nicotine dependence [34, 44]; and anti-social personality disorders [34]. Clinical studies identified substance abuse [38, 47]; alcohol abuse [47]; and other mental disorders [38].…”
Section: Resultsmentioning
confidence: 99%
“…In the studies examined for the present review, remission from pathological gambling [53], nicotine dependence [34], and substance use [43] was associated with improved PTSD outcomes in AI/ANs. Three studies suggested that traditional Native spiritual practices appear to have a protective effect [32, 56, 57].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, research results from Westermeyer et al (2006) found that an absence of stress appeared to be related to a reduction in gambling. In a sample of over 1,600 Aboriginal veterans in the US, remission from a lifetime diagnosis of problem gambling (no gambling symptoms in the past year), using the Diagnostic Interview Schedule for DSM-III-R (APA 2000), was associated with a lack of stress and post traumatic stress (Westermeyer et al 2006).…”
Section: The Hostmentioning
confidence: 96%
“…In a sample of over 1,600 Aboriginal veterans in the US, remission from a lifetime diagnosis of problem gambling (no gambling symptoms in the past year), using the Diagnostic Interview Schedule for DSM-III-R (APA 2000), was associated with a lack of stress and post traumatic stress (Westermeyer et al 2006). Stress appears to be closely bound to initiating and maintaining problem gambling for some Aboriginal gamblers and an absence of stress appears to reduce this risk.…”
Section: The Hostmentioning
confidence: 99%
“…This interest grew out of the apparent aversion of these two groups to seek mental health services in Veterans Administration (VA) settings (Westermeyer, Canive, Garrard, et al, 2002;. Serendipitously, this VAfunded study circled around to a study of behavior-related disorder, this time Pathological Gambling (Westermeyer, Canive, Garrard, Thuras, & Thompson, 2005;Westermeyer, et al, 2006). I am currently conducting another VA-funded study on the epidemiology of gambling problems among veterans.…”
Section: American Indians and Alcohol Abuse-dependencementioning
confidence: 99%